This moment is special : a Día de Muertos story - Parra, John (Simon & Schuster Books for Young Readers, 2025)
"A single day in a boy's life is filled with family, love, and inspiration as he prepares for the Día de Muertos celebration and remembers that all moments are special. Each moment reminds us of our family and those who have gone before us. Today holds a special promise, una promesa especial."--